Формування інституту обмежень і обтяжень в Україні - Коноплянник, М. І.; Бутенко, Євген Володимирович (НУБіП України, 2023)
This thesis highlights the importance of an institutional approach to solving the problems of environmental protection in agriculture and protecting agricultural landscapes from degradation. Institutional changes are aimed at creating new economic relations that will contribute 119 to the intensification of the use of land resources in sustainable development. Prospects include the creation of new social institutions that will regulate complex tasks in production, economy, social spheres and ecology. This approach proposes establishing a single system of rules for all participants in society, including the state and citizens, in order to ensure sustainability and efficiency. The institutional approach contributes to the formation of restrictions and burdens in land use, aimed at ensuring the ecological and economic security of the country.
Keywords: інститут обмежень; земельне законодавство; інститут обтяжень; Einführung von Beschränkungen; institution of restrictions; institute of encumbrances; Grundpfandrechtsinstitut; Bodenrecht; land legislation